A Desolvated Solid–Solid Interface for a High‐Capacitance Electric Double Layer. Issue 12 (4th February 2019) - Wang, Yu‐Zuo; Shan, Xu‐Yi; Ma, Li‐Po; Wang, Jia‐Wei; Wang, Da‐Wei; Peng, Zhang‐Quan; Cheng, Hui‐Ming; Li, Feng
Abstract: Understanding the electric double layer is essential for achieving efficient electrochemical energy storage technologies. A conventional solid–liquid electrode interface suffers from serious self‐discharge and a narrow voltage window, which makes the development of a solid–solid interface imperative. However, an in‐depth understanding of the electric double layer with a solid–solid interface is lacking. Here, a solid–solid interfacial electric double layer is proposed with excellent electrochemical performance. The solid layer is constructed by the electrochemical decomposition of lithium difluoro(oxalate)borate, which provides a desolvated environment for the establishment of a electric double layer. This makes a stronger interaction between the electrode surface and the ions. Based on this unique property, it is found that the solid–solid interfacial electric double layer has an increased capacitance, which suggests a way to develop high‐energy electrochemical capacitors. Abstract : A solid–solid interfacial electric double layer is proposed by a preliminary electrochemical coating. The desolvated environment within the solid–solid interface causes a stronger interaction between the electrode surface and the ions. Based on this unique property, it is found that the solid–solid interfacial electric double layer has an increased capacitance, which suggests a way to develop high‐energy electrochemical capacitors.